COMPARISON OF SOME ANTHROPOMETRIC MEASURES AND MOTOR ABILITIES BETWEEN ALPINE AND SPORT CLIMBERS - Stojan Burnik; Blaž Jereb (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The purpose of our study was to establish the differences in some anthropometric measures and motor abilities between mountaineers and sport climbers. Our sample consisted of 11 top mountaineers and 12 members of A and B national teams in sport climbing. The survey was carried out by means of a standard battery of tests. Anthropo- metric measures were represented by 5 variables, while motor abilities were represented by 14 variables. Motor ability tests were divided into two groups due to a large number of variables. Mobility was surveyed with 6 tests and strength with 8 tests. The data we- re processed with statistical programme package SPSS with the method of discriminant analysis. Discriminant analysis was made separately of anthropometry, mobility and strength. Discriminant function statistically significantly divides mountaineers from sport climbers in anthropometric measures as well as mobility. In the field of strength, stati- stically significant differences between mountaineers and sport climbers were not indi- cated.